STRATEGY TO EFFECTIVELY MAKE E-KTP BY THE POPULATION AND CIVIL REGISTRATION OFFICE OF NAGEKEO DISTRICT - Frederikus Antonius Mana; Syahrabuddin H. Enala; Muhammad N. Prasetya; Rachmat AP. Parukka (Nusantara Hasana Journal, 2024)
Effective and efficient public service is one of the main objectives of the government in organizing government. One form of important public service is the issuance of Population Identification Cards (E-KTP) by the Population and Civil Registration Service (Dukcapil). This study aims to analyze the implementation of the "jemput bola" strategy in improving the quality of E-KTP issuance services at Dukcapil Nagekeo Regency. The research method used is a qualitative method with a case study approach. Data collection was carried out through interviews, observations, and documentation studies. The results of the study indicate that the implementation of the "jemput bola" strategy at Dukcapil Nagekeo Regency has been running quite well. This strategy has proven effective in increasing public accessibility to E-KTP issuance services, especially for people living in remote or hard-to-reach areas. However, there are still several obstacles faced, such as limited human resources and infrastructure, as well as suboptimal coordination between Dukcapil and the village/district government. The recommendations that can be given are the need to increase the number of "jemput bola" officers, improve infrastructure, and improve coordination between Dukcapil and the village/district government to reach the entire community in making E-KTP.